Journal of Cellular Signaling 2020
DOI: 10.33696/signaling.1.013
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sphingolipid Signaling in Glomerular Diseases: Focus on DKD and FSGS

Abstract: Sphingolipids are well-recognized as major players in the pathogenesis of many human diseases, including chronic kidney disease. The kidney is a very sensitive organ to alterations in sphingolipid metabolism. The critical issues to be addressed in this review relate to the role of sphingolipids and enzymes involved in sphingolipid metabolism in the pathogenesis of glomerular diseases with a special focus on podocytes, a key cellular component of the glomerular filtration barrier. Among several sphingolipids, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 109 publications
1
10
0
Order By: Relevance
“…Similar increases in LPE levels were found in an in vivo acute kidney injury model caused by ferroptosis where Gpx4 was deleted [ 37 ]. Pathological role for sphingolipids in diabetic kidney diseases has also been suggested before [ 51 , 52 ], thus it is not surprising that we found a specific species in diabetic kidneys of the db/db model. Similar to oxidized PE, the area where sphingolipids were identified largely correlated with the area of immune cell infiltration areas.…”
Section: Discussionsupporting
confidence: 81%
“…Similar increases in LPE levels were found in an in vivo acute kidney injury model caused by ferroptosis where Gpx4 was deleted [ 37 ]. Pathological role for sphingolipids in diabetic kidney diseases has also been suggested before [ 51 , 52 ], thus it is not surprising that we found a specific species in diabetic kidneys of the db/db model. Similar to oxidized PE, the area where sphingolipids were identified largely correlated with the area of immune cell infiltration areas.…”
Section: Discussionsupporting
confidence: 81%
“…Another study verified increased S1P-mediated inflammation and fibrosis in tubular injury in diabetic nephropathy [ 36 ]. S1P is primarily produced by erythrocytes, and its concentration in blood and tissue is considered a biomarker for some diseases [ 37 ]. This study found decreased levels of S1P in DKD patients, consistent with the finding from KEGG pathway analysis, suggesting impaired S1P-S1PR1 signaling in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…From the sphingolipid metabolism graph, we also see that phytosphingosine, sphingaine, and sphingomyeline have different degrees of aggregation. These metabolites were related to the regulation of renal function during RF [ 23 ]. In our study, the level of PC (20 : 5 (5Z, 8Z, 11Z, 17Z)/(20 : 5 (5Z, 8Z, 11Z, 17Z)) was obviously increased in clinical patient with RF, suggesting that RF might be accompanied with glycerophospholipid metabolism disorder.…”
Section: Discussionmentioning
confidence: 99%